Innovation Performance of Emerging Market Enterprises: The Role of Host-Country Technological Environment - Wang, Luohan (2022)
Using a sample of 341 Chinese high-tech manufacturing multinational companies during 2013-2017, based on the organizational learning theory, this dissertation examines the moderating effect of the host country's technological environment (i.e. technological development level and intellectual property protection) on the benefit of the EME's internationalization on its innovation performance using a two-way fixed effects regression model. The result shows that the host country’s technological development level has a positive moderating influence on this effect, while the host country's intellectual property protection will hinder the benefit of the EME's internationalization on its innovation performance. Besides, although not supported, this dissertation also attempts to explore whether the firms' absorptive capacity can contribute to the positive moderating role of the host country's technological development level. These findings enrich the research on the influence of the host country's technological environment on the relationship between EMEs' internationalization and innovation performance.